Swelling behaviors of porous lignin based poly (acrylic acid). (November 2016) - Ma, Yanli; Sun, Yajie; Fu, Yujie; Fang, Guizhen; Yan, Xingru; Guo, Zhanhu
Abstract: Supramolecular cross-linked porous lignin based poly (acrylic acid) [LBPAA] was lab-synthesized by copolymerizing lignin grafted N, N'-methylene-bisacrylamide (LM) and acrylic acid. LBPAA successfully acted as a water retention agent with salt resistance and biodegradation for agricultural applications. Lignin was found to improve its swelling behaviors with higher water retention, fast swelling and de-swelling rates. The salt tolerance was stronger in the case of LBPAA (60 PAA/40 LM) [60 wt% PAA/40 wt% LM], i.e., 145.79 g·g −1 higher than PAA at 0.09 mM KCl solution. The effect of ion charges on the LBPAA swelling ratio was greater than that of ionic radius. The weight loss of LBPAA (60 PAA/40 LM) was 5.47%, 4.96%, and 4.56% in the soil of Tangshan, Harbin, and Sian, respectively. The soil moisture content and clay content were observed to decrease gradually with increasing the burial time. The biodegradation test of LBPAA (60 PAA/40 LM) composite exhibited different bacterial colony forming units (CFU), the soil of Tangshan was 2.0 × 10 3  CFU·g −1 soil, 7.0 × 10 3  CFU·g −1 soil for Harbin, and 6.10 × 10 4  CFU·g −1 soil for Sian. However, the organic matter contents in the soils did not have significant changes (Tangshan 6.21 mg·g −1, Harbin 0.61 mg·g −1, and Sian 0.405 mg·g −1 ). Graphical abstract: Lignin from wood, straw, and paper industry was introduced to porous polyacrylic acid composite hydrogel, demonstrating higher water retention, salt resistance and biodegradation. Highlights: Lignin based poly (acrylic acid) (LBPAA) was synthesized by free radical-initiated copolymerization. LBPAA with pores improved water retention, salt resistance and biodegradation. LBPAA had no significant effects on the organic matter content and bacterial colony forming units of soil. Lignin was found to improve swelling behaviors with higher water retention, fast swelling and de-swelling rates.